2022
DOI: 10.18087/cardio.2022.5.n1755
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ adherence to the guidelines on the chronic heart failure diagnosis and treatment

Abstract: Aim      To evaluate the physician’s knowledge of basic provisions of clinical guidelines for diagnosis and treatment of chronic heart failure (CHF) and to determine how the actions of physicians in their everyday clinical practice comply with these provisions.Materials and methods The study analyzed anonymous questionnaires of 185 physicians (127 cardiologists, 40 internists and general practitioners, 18 other specialists) who were trained in advanced training programs during the 2020/2021 academic year. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
2
0
0
1
Order By: Relevance
“…Interventions such as guideline dissemination and education have been shown to improve adherence to cardiovascular disease guidelines [24]. We suggest that the provision of suitable training might improve physicians' knowledge of GDMT for HFrEF, in agreement with a previous report that recommended training programs focusing on the use of medications such as RAS inhibitors and beta-blockers, dosing principles, and the indications for ICD placement [21]. The provision of training programs is particularly important given that nearly half of the physicians surveyed in this study reported not taking a proactive approach to learning about GDMT for HFrEF and given that more than half of the respondents saw only a small number of patients with HFrEF each month, limiting their clinical experience.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Interventions such as guideline dissemination and education have been shown to improve adherence to cardiovascular disease guidelines [24]. We suggest that the provision of suitable training might improve physicians' knowledge of GDMT for HFrEF, in agreement with a previous report that recommended training programs focusing on the use of medications such as RAS inhibitors and beta-blockers, dosing principles, and the indications for ICD placement [21]. The provision of training programs is particularly important given that nearly half of the physicians surveyed in this study reported not taking a proactive approach to learning about GDMT for HFrEF and given that more than half of the respondents saw only a small number of patients with HFrEF each month, limiting their clinical experience.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, less than half of the respondents were aware of the indications for CRT or ICD use in patients with HFrEF, in agreement with a previous study [21], implying that these treatments may be underused in eligible patients in China. Indeed, the China Heart Failure study showed that ACEIs/ARBs, beta-blockers and MRAs were utilized in only 27%, 25.6% and 26.6%, respectively, of patients with HF at admission to hospital, while ICDs, CRT and other devices were utilized in only 0.3% of patients hospitalized for HF [22].…”
Section: Discussionsupporting
confidence: 81%
“…В то же время, как и в отношении приверженности больных, отсутствуют утвержденные терминология и методология определения приверженности/неприверженности врачей [10]. В целом ряде российских и зарубежных исследований была продемонстрирована недостаточная приверженность врачей положениям современных КР, выявлены нерациональные, ошибочные назначения ЛП при лечении пациентов с ХНИЗ [11][12][13][14][15][16].…”
Section: Introductionunclassified